AN ANALYSIS OF STUDENTS’ CONFIDENCE IN SPEAKING ENGLISH TOWARDS VOCABULARY MASTERY AT SMPN 35 MAKASSAR - Yetti, Teresia; Rampeng, Rampeng; Sahib , Nurfaizah (Lembaga Jurnal FKIP Universitas Bosowa, 2024)
The objectives of this research is to to find out why students are not confident in speaking English even though they have a lot of vocabulary at Smpn 35 Makassar. This research used qualitative method. This research was conducted in three stages, namely observation, questionnaire and interview test. The samples of this study were students of class VIII-4, namely 25 students as respondents and an English teacher of class VIII-4. Data collection used observation, questionnaire and interview test. The result of this study is that the amount of vocabulary that students have does not guarantee that a student is confident in speaking English. this is caused by shyness, fear of being wrong and the influence of the environment, where the environment is very influential in building students' confidence to speak. Based on the results of research conducted in class VIII-4 SMPN 45 Makassar, based on the results of the questionnaire, there are 15 students who feel embarrassed if they make mistakes and 10 students who do not feel embarrassed if they make mistakes in speaking English.